2007
DOI: 10.1017/s1355617707070981
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal reliance on object structure in apraxics' learning of novel object-related actions

Abstract: We assessed the prediction that object structural cues could benefit the learning of object-action relationships in ideomotor apraxia (IMA). A total of 15 patients with left-hemisphere stroke, 11 of whom exhibited IMA, and 10 healthy subjects were trained to match novel gestures to novel tool pictures that were either High- or Low-Afforded by their associated tools. Learning was assessed with recognition and production tests. Only IMA patients demonstrated better recognition of High- than Low-Afforded gestures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 44 publications
1
22
0
2
Order By: Relevance
“…Specific to the current work, damage to superior temporal cortex has been associated with a selective loss of tool-related knowledge (Tranel et al, 1997a). This is supported by clinical studies which show apraxic patients with lesions focused at superior temporal gyrus benefit from high levels of object affordance in gesture recognition (Barde et al, 2007). In other words, damage to superior temporal areas in the presence of spared dorsal areas specifically impacts the understanding of tool function.…”
Section: Discussionmentioning
confidence: 77%
“…Specific to the current work, damage to superior temporal cortex has been associated with a selective loss of tool-related knowledge (Tranel et al, 1997a). This is supported by clinical studies which show apraxic patients with lesions focused at superior temporal gyrus benefit from high levels of object affordance in gesture recognition (Barde et al, 2007). In other words, damage to superior temporal areas in the presence of spared dorsal areas specifically impacts the understanding of tool function.…”
Section: Discussionmentioning
confidence: 77%
“…A study from our laboratory (Barde, Buxbaum, & Moll, 2007) (reviewed by O + B) provides evidence that at least some apraxics exhibit deficits in motor learning, and abnormal reliance on affordances during learning. Patients with left hemisphere stroke, with and without apraxia, were trained to perform and recognize the actions associated with novel tools over multiple trials.…”
Section: Evidence Claimed By Osiurak and Badets As Contrary To The mentioning
confidence: 99%
“…Several patient studies have illustrated dissociations between mechanical problem solving skills and action semantics on object use [Bartolo et al, 2007;Goldenberg and Hagmann, 1998;Hodges et al, 2000]. Recent research on the learning of novel objectrelated actions has indeed shown that patients with IMA benefit from the affordance of the gesture compared to non-IMA patients and normal controls, suggesting that IMA patients are strongly reliant on object structure in gesture recognition [Barde et al, 2007]. These studies suggest that the human ability to work with tools and objects is reliant on different neural entities that each contribute to an adequate tool-to-goal related behavior and, when damaged, may be (partly) compensated by the intact parts of the network.…”
Section: Pantomiming the Use Of Familiar Versus Unfamiliar Toolsmentioning
confidence: 99%